Using Evidence to Scale Up Innovation : Insights from a Results-Based Financing Project for Health in Zambia - Qamruddin, Jumana (International Finance Corporation, Washington, DC, 2014)
Several developing countries face the challenge of attaining sufficient population level impact to meet health-related Millennium Development Goals (MDGs). This situation is partly attributable to constraints in their health systems, including: severe shortages in human resources for health; inequalities in service provision and utilization; limited financial resources; and inefficiencies in resource allocation and use. Even in countries with adequate financial resources, health indicators are sometimes poor due to inefficiencies and a lack of performance related initiatives. In an attempt to strengthen health systems and improve health-service delivery, several countries in Africa are increasingly using Results-Based Financing (RBF) approaches in their health programs. The premise is that linking financing to results will lead to improvements in health systems and health-outcome indicators. This paper captures emerging lessons from Zambia's drive to improve service delivery in the public-health sector with support from the World Bank's RBF initiative.